43.3k views
20 votes

x - 1 = \sqrt{ (y + 7)/(2) }


User Toyo
by
4.9k points

1 Answer

6 votes

Solving for x:


x = \sqrt{ (y + 7)/(2) } + 1

Explanation:

1) Just add 1 to both sides.

Solving for y:


y = 2( {x}^(2) - 2x + 1) - 7

Step by step explanation:

1) Square both sides.


{x}^(2) - 2x + 1 = (y + 7)/(2)

2) Multiply both sides by 2.


( {x}^(2) - 2x + 1) * 2 = y + 7

3) Regroup terms.


2( {x}^(2) - 2x + 1) = y + 7

4) Subtract 7 from both sides.


2( {x}^(2) - 2x + 1) - 7 = y

5) Switch sides.


y = 2( {x}^(2) - 2x + 1) - 7

Therefor, the answer for Y is y = 2 ( x² - 2x + 1) -7.

User Jerseyboy
by
5.3k points